Nutrition Screening Training for Young Women in School Health Organizations Using the Media Screenzi Training Module - Dominika; Desi (Jurnal teknologi Kesehatan Borneo, 2022)
Nutritional problems that often occur in adolescent girls are nutrient intake, which can cause chronic lack of energy and anaemia. These problems will hurt health levels, for example, the risk of giving birth to a baby with low birth weight (LBW). One of the ways that can be done to prevent and overcome nutrition problems in adolescent girls is with nutrition education and training. This study's purpose is to know the influence of nutritional screening training for adolescent girls in the School Public Health organisation using the SMA 01 Serawai Sintang Regency screen training module. This study is a pre-experimental study with one group pre and post-test design; the sample of this study was 30 respondents. Data was taken using a questionnaire and observation sheet and analysed using univariate and bivariate analysis. The results of this study indicate there are significant differences in nutritional knowledge before and after nutrition screening training (p = 0,000), there are differences in the ability in anthropometric measurements of respondents before and after nutrition screening training (p = 0,000), and on the ability to determine nutritional status, there were also significant differences before and after nutrition screening training (p = 0,000).